Kedekatan Emosional Polri terhadap Masyarakat dalam Merespons Program Prioritas Kapolri terkait Pemantapan Komunikasi Publik, Perspektif Ilmu Psikologi: Kedekatan Emosional Polri terhadap Masyarakat dalam Merespons Program Prioritas Kapolri terkait Pemantapan Komunikasi Publik, Perspektif Ilmu Psikologi - Agung - Himawan (Jurnal Litbang Polri, 2023)
ABSTRACT The purpose of this study is to describe the steps and achievement indicators of the National Police, especially the Surabaya Polrestabes, in building Polri's emotional closeness to the community in order to respond to the Chief of Police's priority programs related to strengthening public communication. This research is a type of qualitative descriptive research, where the data sources are primary and secondary data and data collection techniques by way of literature study, interviews, documentation and observation. After the data was collected, it was analyzed using the instrument presented by Antin, L. (2016) related to meeting the emotional needs of individuals with emotional closeness and Stewart L. Tubbs & Sylvia Moss, (2009) regarding indicators of achieving effective public communication in order to obtain answers to research questions. The results of the study found that (1) the steps taken by the Surabaya Polrestabes related to individual emotional needs have gone well which are characterized by behavior supporting and accompanying residents, behavior of sympathy and empathy, responding to complaints and complaints from the community as well as finding and finding solutions, being able to provide support to community achievers and channel hobbies and interests; (2) indicators of achievement of public communication by Polrestabes Surabaya towards community members, as a result of the building of emotional closeness can be seen from a number of face-to-face activities such as Confide Fridays, Friday blessings, Sambang Patrols and so on, where Polri personnel have listened to residents' complaints properly and when asked by residents for advice, able to try to find and find solutions related to the cause of a citizen's problem, Polri personnel are able to take action and influence the attitude of citizens to jointly maintain security and order, Polri personnel are able to improve cohesiveness and social relations between citizens. Keywords: emotional closeness, public communication, maintenance and public order